Guiding Students to Become Young Entrepreneurs Through School Entrepreneurship Education - Alim Ikmal Jamal; Wahira Wahira (Journal of Educational Development and Learning (JEDAL), 2024)
Entrepreneurship education in schools has a very important role in preparing the young generation to become independent and innovative entrepreneurs. By introducing entrepreneurial concepts from an early age, students can be taught to recognize opportunities, manage risks, and build the skills needed to create their own businesses. This research aims to explore the ways in which entrepreneurship education in schools can guide students to become successful young entrepreneurs. The method used in this study is a literature study that includes various theories and practices of entrepreneurship applied in schools in Indonesia. The results show that effective entrepreneurship education can encourage students to develop business ideas, increase their confidence, and prepare them to face the challenges of the business world.